Ergonomic Factors on The Purchase Decision of Matic Motorcycles - Ermayana Megawati; Wahyu Sidiq Saputra; Hendrik Cahya Prabowo; Firman Ardiansyah Ekoanindiyo (STIE AAS Surakarta, 2021)
Motorcycles are a practical and economical means of transportation to use. People prefer to use private vehicles because the mass transportation system in Indonesia is not yet good. There is a discrepancy between the size of the motorcycle seat and the static seat anthropometry of students. This mismatch can result in ergonomic risks to the driver and result in traffic accidents. In the Central Java area, especially the city of Kendal, there is a high interest in this mode of transportation. The people have diverse tastes in the selection of motorbikes, some prefer automatic motorbikes and some prefer sport motorbikes. The decision in buying a motorcycle has several considerations made by consumers before deciding to buy a motorcycle, including ergonomics. How to get information by using a questionnaire or questionnaire. Using validity and testing. From the results of the validity test with the purchase of an automatic motorcycle, all indicators are valid, so it is stated that it is appropriate to buy an automatic motorcycle. With a reliable test with the purchase of an automatic motorcycle, all indicators are reliable, so it is declared consistent in product purchases.